Abnormal Behavior Episodes Associated With Zonisamide in Three Dogs: A Case Report - Kanazono, Shinichi; Ukai, Masayasu; Hiramoto, Akira (Frontiers in Veterinary Science, 2021)
Psychiatric adverse effect associated with anti-seizure drugs has been well recognized in human medicine. This case report describes three dogs with presumptive idiopathic epilepsy presented for abnormal behavior episodes. Abnormal behavior episodes included sudden rage and aggression to the family members, insomnia, restlessness, and/or constant attention seeking behavior. Magnetic Resonance Imaging study and cerebrospinal fluid analysis in two dogs were unremarkable. The abnormal behavior episodes deteriorated along with gradual dose increment of zonisamide and these episodes almost completely disappeared within 5 days after discontinuation of zonisamide. The exact same episodes relapsed within days after re-administration of zonisamide and disappeared again shortly after discontinuation of zonisamide. Dose adjustments of other antiseizure medications in Case 2 did not result in significant changes in these behavior episodes. Although psychiatric adverse effects including aggressive behavior associated with zonisamide are widely recognized in humans, this is the first report in dogs in the clinical setting.